Takis - Brett, Guy 1942-2021; Wellen, Michael (Tate, 2019)
One of the most playful, innovative and eccentric artists of Postwar Europe, Takis (b.1925, Athens) was a catalysing figure in the artistic and literary circles of Paris, London and New York from the 1950s onward. Pioneering a variety of sculpture, painting and musical structures, Takis made works that harness invisible natural forces. Perhaps best known are his innovative 'telemagnetic' works, begun in the late 1950s using everyday metallic objects that float in space through the use of magnets. These investigations and his fierce individualism won him the admiration of Beat writers such as Allen Ginsberg and William Burroughs and caused polemics with his artistic contemporaries Yves Klein, Giacometti and Jean Tinguely. This publication will be the first English-language introduction to a key figure of Europe's post-war avant-garde and cultural underground. Through a combination of new essays and a key selection of primary sources, this publication will foreground the artist's influence in contemporary art since the 1960s - and it's accessible and thematic approach will expand the audience for this book far beyond the specialist. Exhibition: Tate Modern, London, UK (03.07.-27.10.2019)
Impressum: First published ... on the occasion of the exhibition "Takis", Tate Modern, London 3 July - 27 October 2019, MACBA, Barcelona, 21 November 2019 - 19 April 2020, Museum of Cycladic Art, Athens, 20 May - 25 October 2020
Includes bibliographical references
Keywords: Takis -- 1925-2019; Kinetische Kunst; Takis / 1925- / Exhibitions; Ausstellungskatalog -- Tate Modern -- 03.07.2019-27.10.2019 -- London; Ausstellungskatalog -- Museu d'Art Contemporani de Barcelona -- 21.11.2019-19.04.2010 -- Barcelona; Ausstellungskatalog -- Museum of Cycladic Art -- 20.05.2020-25.10.2020 -- Athen; Bildband